A implementação do princípio da reunificação familiar para proteger deslocados internos ambientais no méxico e na colômbia (1998-2024) - Santos, Lara Cecília Araújo dos (2026)
Inernal displacement, particularly that resulting from environmental change, has become a growing global challenge. This research analyzes the implementation of the family reunification principle, one of the 1998 Guiding Principles on Internal Displacement, as a protection mechanism for environmentally displaced persons in Mexico and Colombia between 1998 and 2024. The study employs an exploratory, qualitative, and bibliographic approach, utilizing academic literature, legal norms, and public policies. Through a multiple case study method, it identifies challenges and actions to gain a deeper understanding of the phenomenon. Theoretically grounded in the humanitarian protection literature, especially the contributions of Zetter (2015), the author seeks to broaden the debate on protection and environmental displacement in Latin America, highlighting the practical application of the principles. The study concludes that, although present in a significant portion of the analyzed documents, family reunification does not represent a priority for Mexico and Colombia when dealing with internally displaced persons in the context of environmental change. Presented in a brief and generic manner, without assigning responsibilities to specific actors and with few concrete actions, this principle proves to be quite limited in terms of protecting the group under study.